PENGARUH VEGETASI PIONIR TERHADAP KELIMPAHAN BAKTERI AMONIFIKASI DAN KADAR KARBON ORGANIK TANAH DI LAHAN BEKAS TAMBANG BATUBARA PT. BERAU COAL KALIMANTAN TIMUR - , Arom Figyantika, Handojo Hadi Nurjanto, Haryono Supriyo ([Yogyakarta] : UIN Maulana Malik Ibrahim, 2009)
Vegetation type and litter quality have important effect to soil microorganisms that have important roles in the soil development at the post coal mining landscape than the substrate. The objectives of this research were to assess the effect of pioneer vegetation to the soil organic carbon content, the abundance of total bacteria and ammonification bacteria at the post coal mined land PT. Berau Coal in East Kalimantan, to obtain ammonification bacteria, and determinate it. Soils were collected from rehabilitated area of PT, Berau Coal in Binungan, Lati and Sambarata sites. Soil samples were taken from surface soil (0-5 cm) under crown of Trema cannabina (TC), Macaranga conifera (MC) and Macaranga triloba (MT). Population of ammonification bacteria was assessed using Most Probable Number method, and the soil organic carbon content was assessed using Walkey and Black method. Isolation and determination of the bacteria were done using standard methods The result showed that the content of soil organic carbon, the abundance of total bacteria and ammonification bacteria were affected by pioneer vegetation. They were greater than in soil without vegetation. The greatest soil organic carbon content (0,39%), total bacteria (2,5x10 &#8309